Perencanaan dan Pengelolaan Keuangan Keluarga di Masa Pandemi Covid-19 - Rita Rahayu; Verni Juita; Denny Yohana; Annisa Rahman; Rahmat Febrianto (Warta Pengabdian Andalas, 2022)
This activity aims to provide training and understanding to the community on the importance of family financial planning and management. This activity was motivated by the current conditions of the Covid-19 pandemic. When the wheels of the economy became disrupted, many companies went out of business and went bankrupt, resulting in many companies that laid off their employees. This will undoubtedly have a significant impact on disrupting the family economy on a small scale and the country's economy on a larger scale. Therefore, this service activity needs to be carried out because, through the ability to plan and manage sound finances, it is believed that it will help the family in planning their grievances so that financial problems can be minimized. The activities carried out were workshops and seminars involving homemakers in Padang. The selection of homemakers in this activity was because a mother is a financial manager in a family. So that the mother's ability to manage finances determines the family's financial condition, this activity was carried out for one day. The result of this activity was an increase in the ability of homemakers to manage and plan finances.